Synaptic Organization of Microglomerular Clusters in the Lateral and Medial Bulbs of the Honeybee Brain - Theo Mota; Theo Mota; Theo Mota; Sabine Kreissl; Ana Carrasco Durán; Ana Carrasco Durán; Damien Lefer; Damien Lefer; Giovanni Galizia; Martin Giurfa; Martin Giurfa (Frontiers in Neuroanatomy, 2016)
The honeybee Apis mellifera is an established model for the study of visual orientation. Yet, research on this topic has focused on behavioral aspects and has neglected the investigation of the underlying neural architectures in the bee brain. In other insects, the anterior optic tubercle, the lateral and the central complex are important brain regions for visuospatial performances. In the central brain of the honeybee, a prominent group of neurons connecting the anterior optic tubercle with conspicuous microglomerular synaptic structures in the lateral complex has been recently identified, but their neural organization and ultrastructure have not been investigated. Here we characterized these microglomerular structures by means of immunohistochemical and ultrastuctural analyses, in order to evaluate neurotransmission and synaptic organization. Three-dimensional reconstructions of the presynaptic and postsynaptic microglomerular regions were performed based on confocal microscopy. Each presynaptic region appears as a large cup-shaped profile that embraces numerous postsynaptic profiles of GABAergic tangential neurons connecting the lateral complex to the central complex. We also identified serotoninergic broad field neurons that probably provide modulatory input from the central complex to the synaptic microglomeruli in the lateral complex. Two distinct clusters of microglomerular structures were identified in the lateral bulb and medial bulb of the lateral complex. Although the ultrastructure of both clusters is very similar, we found differences in the number of microglomeruli and in the volume of the presynaptic profiles of each cluster. We discuss the possible role of these microglomerular clusters in the visuospatial behavior of honeybees and propose research avenues for studying their neural plasticity and synaptic function.